Pensions and public servants. A study of the origins of the British system (Mouton, 1964)
- With bibliogr., ills, index and tabs. Publications of the Social Sciences Center, Athens. Publ. in collaboration with the École Pratique des Hautes Études, Sorbonne, VIe, Sciences Économiques et Sociales. 3.